THE VALUE OF POLYMORPHISM RRO12ALA GENE PPARG IN VIOLATION OF LIPID PEROXIDATION AND ANTIOXIDANT PROTECTION IN PATIENTS WITH TYPE 2 DIABETES - V. Y. Mokrii; S. V. Ziablytsev; M. V. Cryshtal (Bogomolets National Medical University, 2016)
Resume. The incidence of type 2 diabetes is increasing in Ukraine and worldwide. The severity of this disease is determined by the number of complications, which are based on lipid peroxidation (LPO). Today, the influence of gene polymorphisms Pro12Ala PPARG on oxidative and antioxidant processes is not in doubt. We studied the association between gene polymorphism Pro12Ala rs1801282 PPARG and intensification of lipid peroxidation and antioxidant systems (AOS) in 88 patients with type 2 diabetes, using analysis of variance. In the 12Pro allele carriers male found probable increased intensification of lipid peroxidation than in women, with increasing levels of DC (p=0,034) and MDA (p=0,001). Reducing the enzyme catalase level of AOC in patients with type 2 diabetes was observed in the case of genotype Pro12Pro gene PPARG on 21.7% compared with heterozygotes (F=8,17; p=0,005) and the presence of the allele 12Pro (F=6,28 , p=0,013). Found significantly higher activity of AOC in the form of increasing the level of 6-TF (p=0,016) and catalase activity (p=0,034) among male patients with gene polymorphism Pro12Ala PPARG, than homozygotes for allele 12Pro.